2016
DOI: 10.1136/annrheumdis-2016-209154
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids are associated with a lower prevalence of autoantibodies in shared epitope-positive subjects at risk for rheumatoid arthritis

Abstract: Objectives Previously, we found that omega-3 fatty acids (n-3 FAs) were inversely associated with anti-cyclic citrullinated peptide (anti-CCP) positivity in participants at risk for future rheumatoid arthritis (RA). We investigated whether n-3 FAs were also associated with rheumatoid factor (RF) positivity and whether these associations were modified by shared epitope (SE) positivity. Methods The Studies of the Etiology of RA (SERA) cohort includes RA-free participants who are at increased risk for RA. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 44 publications
(53 reference statements)
3
54
0
5
Order By: Relevance
“…Fish intake may exert a protective effect on RA by the anti-inflammatory effects of omega-3 polyunsaturated fatty acids [2]. Among at-risk individuals, erythrocyte membrane-bound omega-3 PUFA levels were inversely associated with anti-CCP/RF positivity [15]. Previous studies investigating EDIP found robust associations between EDIP scores and colorectal cancer risk but no association with ovarian cancer risk [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Fish intake may exert a protective effect on RA by the anti-inflammatory effects of omega-3 polyunsaturated fatty acids [2]. Among at-risk individuals, erythrocyte membrane-bound omega-3 PUFA levels were inversely associated with anti-CCP/RF positivity [15]. Previous studies investigating EDIP found robust associations between EDIP scores and colorectal cancer risk but no association with ovarian cancer risk [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a finding that has been relatively consistent across many studies is that a higher intake of fish as well as omega-3 fatty acids have been consistently linked to decreased risk for RA across a number of studies, including studies where dietary data was collected prior to incident RA (8488). Furthermore, in FDRs of patients with RA who at the time of study did not have classifiable RA, self-reported intake of supplements containing omega-3 fatty acids, as well as biomarkers of fatty acids, found that increased intake and higher blood levels of fatty acids were associated with decreased risk for RF and ACPA positivity (89, 90). Notably, there appeared to be a greater protective effect in individuals who were positive for at least one allele containing the SE, suggesting that there may be an interaction between these factors in mediating RA risk (89).…”
Section: Environmental Risk Factors For Ramentioning
confidence: 99%
“…Furthermore, in FDRs of patients with RA who at the time of study did not have classifiable RA, self-reported intake of supplements containing omega-3 fatty acids, as well as biomarkers of fatty acids, found that increased intake and higher blood levels of fatty acids were associated with decreased risk for RF and ACPA positivity (89, 90). Notably, there appeared to be a greater protective effect in individuals who were positive for at least one allele containing the SE, suggesting that there may be an interaction between these factors in mediating RA risk (89). These findings coupled with clinical trials where fatty acid intake is associated with decreased RA activity in established disease suggest there could be a direct protective relationship of fatty acids across the spectrum of RA development (91).…”
Section: Environmental Risk Factors For Ramentioning
confidence: 99%
“…Behavioral factors, such as smoking, obesity, low fish intake, and poor dental health, are associated with increased RA risk (69). Smoking is the strongest behavioral RA risk factor and prolonged cessation >20 years decreases RA risk to that of never smokers, suggesting that smoking cessation may lower RA risk (6, 10, 11) Increased fish intake is associated with decreased RA risk perhaps due to the anti-inflammatory effects of omega-3 fatty acids (8, 12, 13). Being overweight or obese is associated with increased RA risk (7, 14).…”
mentioning
confidence: 99%